Community library management at Kampung Teroi Bukit / Nurul Anisatul Batrisyia Mohd Zaudi - Mohd Zaudi, Nurul Anisatul Batrisyia (2023)
Kampung Teroi Bukit Community Library is a library located in Yan Kedah. The library was first opened to the public in 2007 after it started operating in 2006. The Kampung Teroi Bukit Community Library still manages library matters manually. Several issues were discovered during an interview with a librarian. Among those issues are guests or members experiencing manual book searches, poor data storage and librarians misfiling borrowed records. As a result, the Community Library Management system in Kampung Teroi Bukit was created to deal with the issues that arise in the current procedures in this library. The objective of this project is to identify the current process of library management system Community Library Kampung Teroi Bukit, to design and develop the system for Community Library Kampung Teroi Bukit and to evaluate the functionality of the system for Community Library Kampung Teroi Bukit. Next, the Adaptation Waterfall model was used as a system approach to develop a Community Library Management system in Kampung Teroi Bukit. There are five steps involved which are analysis phase, design phase, implementation phase, testing phase, and documentation phase. This is because this technique is suitable for small projects such as the Kampung Teroi Bukit Community Library Management System. Following that, Schneirderman's eight golden rules were selected as the theory for the Community Library Management system in Kampung Teroi Bukit in this study. Then, the functional test was done with the supervisor and also 2 librarians from Teroi Bukit Community Library. The results of the study give positive results from the system that has been developed. Finally, it is expected that this system will benefit its users in the present and in the future.